Some effects on reproduction and nursing traits of Hungarian Large White pigs - Bene, Szabolcs; Fekete, Zsuzsanna; Lendvay, Miklós; Rajnai, Csaba; Polgár, Péter J.; Szabó, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
Reproduction and nursing traits was studied in the seedstock Hungarian Large White herd of the University of Pannonia Georgikon Faculty at Keszthely. Data of 64 breeding boars mated to 1000 sows resulting 4155 farrowings were evaluated with sire model.Year of farrowing, season of farrowing, number of farrowing, month of mating as fixed, while sire and seminal boar as a random effect was treated.The aim of the study was to evaluate the effect of genetic or environmental factors on the examined traits (live born piglets, dead born piglets, litter weight at born, average weight at born, mortality in the first 21 days, 21 days piglets, litter weight at 21st day, average weight at 21st day, weaned piglets).The overall mean value of the examined traits were as follows: 9.62 heads; 12.09%; 13.80 kg; 1.45 kg; 12.97%; 7.99 heads; 43.58 kg; 4.97 kg; 7.44 heads.The results of the examination show that the reproduction and nursing traits increased with increasing dam’s age as far as the 4 year age of sows. No significant differences between piglets of 4–7 year age sows were found.The distance among the breeding boars was significantly. The effect of shire in the total variance was 8.35–27.73%.Our results show selection of good sires is very important in the course of breeding.
Keywords: Hungarian Large White pig; reproduction; nursing; effect of boars